The impact of Job Level on Employee performance, Job Satisfaction, Job Stress and Turnover intention of Western UP healthcare employees - Ashi, Nikita Singhal, (European Economic Letters (EEL), 2025)
Stress is now almost an epidemic, as men, women, and children are suffering from it every day. This study seeks to examine stress elements and different coping techniques utilized by healthcare workers. The interaction between employees and the conditions of work resulted in job stress; however, perspectives on causes and effects differ. The purpose of this research is to analyse impact of job level on employee performance, job satisfaction, job stress and turnover intention of Western UP healthcare employees.309 responses are being finalized for the analysis. As per the study findings, Job Stress also shows a negative impact on job satisfaction. But the Job stress shows a positive impact on Turnover. Job level shows a negative impact on Employee Performance. Job level shows a negative impact on Job Stress. Job level shows a positive impact on Job satisfaction. Job level shows a positive impact on Turnover.